1998
DOI: 10.1097/00005344-199811000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Small Doses of Canrenone Block the Effects of Ouabain on the Mechanical Activity of the Heart and Vessels of the Rat

Abstract: Canrenone has been described as an antihypertensive drug that blocks endogenous ouabain effects in volume-dependent hypertensive models. Considering that some canrenone metabolites may be putative mutagenic factors, therapeutic dose reduction might be advantageous if the blockade of ouabain effects is maintained. In this study, the effects of low doses or concentrations of canrenone were investigated in rats by using isolated papillary muscles, Langendorff-perfused hearts, perfused rat-tail vascular bed, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…One of the first clues that canrenone was a CTS receptor antagonist was the ability of therapeutic doses to reduce the effect of digitalis and ouabain on the heart 157162 . Subsequent work showed canrenone suppressed ouabain binding to the Na + pump 163,164 and was antihypertensive in some experimental models of hypertension where ouabain-like factors were implicated 165168 .…”
Section: Implications For Therapymentioning
confidence: 99%
“…One of the first clues that canrenone was a CTS receptor antagonist was the ability of therapeutic doses to reduce the effect of digitalis and ouabain on the heart 157162 . Subsequent work showed canrenone suppressed ouabain binding to the Na + pump 163,164 and was antihypertensive in some experimental models of hypertension where ouabain-like factors were implicated 165168 .…”
Section: Implications For Therapymentioning
confidence: 99%
“…The beneficial effect was initially attributed to the blockade of aldosterone receptor, but some studies have shown a direct effect of spironolactone and its derivative metabolites on cardiac excitation–contraction coupling (Coraboeuf and Deroubaix, 1974; Mugge et al. , 1984; Vassallo et al. , 1998; Cargnelli et al.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports have suggested that canrenone interacts with the digitalis receptor site of the Na + pump and antagonizes the binding of ouabain (19,27). Indeed, acute administration of canrenone blocks the positive inotropic effect of ouabain in isolated perfused hearts (18). To clarify this issue, we first tested the effects of canrenone or canrenone plus ouabain on arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
“…To determine whether the effects of ouabain were caused by inhibition of the Na + pump activity, canrenone (1 mg/ kg) a blocker of ouabain effects, was used because of its antagonistic properties at the digitalis receptor site (18,19). This small concentration of canrenone was used to avoid the changes induced by larger concentrations in myocardial contractility, vascular tone or arterial blood pressure, as previously reported (18).…”
Section: Na + Pump Blockadementioning
confidence: 99%
See 1 more Smart Citation